Panduan untuk menerapkan analisa multikriteria dalam menilai kriteria dan indikator - Mendoza, G.A.; Macoun, P.; Prabhu, Ravi; Sukadri, D.; Purnomo, H.; Hartanto, H. (Center for International Forestry Research, 2000)
Multi-Criteria Analysis (MCA) is a decision-making tool developed for complex problems. In a situation where multiple criteria are involved confusion can arise if a logical, well-structured decision-making process is not followed. Another difficulty in decision-making is that reaching a general consensus in a multidisciplinary team can be very difficult to achieve. By using MCA members do not have to agree on the relative importance of the criteria or the rankings of the alternatives. Each member enters his or her own judgements, and makes a distinct, identifiable contribution to a jointly reached conclusion. This manual is written for an audience that needs a clear, easy to follow manual that can be used in the field to implement MCA. The information is structured so that the reader is first introduced to the general concepts involved before delving into the more specific applications of MCA. The manual reviews the conceptual framework of C&I and introduces the theoretical basis of MCA, and methods such as ranking, rating and pair wise comparisons in the Analytic Hierarchy Process. It provides an example of how MCA can be applied to C&I in a Forest Certification context both from a 'top-down' perspective as well as in a more 'bottom-up' context.